2016
DOI: 10.1071/he15113
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study examining the extent of unwanted sexual attention and unhealthy intimate relationships among female university students

Abstract: Unwanted sexual attention and unhealthy intimate relationships have the potential to have serious negative health consequences. To date, there has been scant focus on these issues among university students in Australia. The aim of the current study was to describe the extent of unwanted sexual attention and unhealthy intimate relationships experienced in their lifetime by female university students aged 18-25 years. A cross-sectional study was undertaken involving 465 female students aged 18-25 years. Students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Holland et al (2017) investigated a broader range of body evaluation behaviors (i.e., gazing, sexual remarks, catcalls/wolf whistles) and found that women report being the target of objectification behaviors once every two days. Studies on sexual harassment (Fairchild, 2010) and unwanted touching (Hayden, Graham, & Lamaro, 2016) also put forward that women are frequently exposed to such behaviors (see also, Gelfand, Fitzgerald, & Drasgow, 1995).…”
Section: Sexual Objectification As a Focus On Physical Appearancementioning
confidence: 99%
“…Holland et al (2017) investigated a broader range of body evaluation behaviors (i.e., gazing, sexual remarks, catcalls/wolf whistles) and found that women report being the target of objectification behaviors once every two days. Studies on sexual harassment (Fairchild, 2010) and unwanted touching (Hayden, Graham, & Lamaro, 2016) also put forward that women are frequently exposed to such behaviors (see also, Gelfand, Fitzgerald, & Drasgow, 1995).…”
Section: Sexual Objectification As a Focus On Physical Appearancementioning
confidence: 99%
“…Research suggests that campus sexual assault is a problem in both the Global South (Ogunwale & Oshiname, 2017; Schuster et al, 2016; D’Abreu et al, 2013; Lehrer, Lehrer, & Koss, 2013) and the Global North (Hayden et al, 2016; Krahé et al, 2015; Valls et al, 2016). Bystander interventions are one of the few prevention methods with some demonstrated efficacy (Banyard et al, 2009; Mabry, A., & Turner, M. M., 2015), and they are being rolled out at many U.S. institutions of higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual assault is a significant public health problem for undergraduates worldwide (D’Abreu, Krahé, & Bazon, 2013; Hayden, Graham, & Lamaro, 2016; Krahé et al, 2015; Ogunwale & Oshiname, 2017; Schuster, Krahé, Ilabaca Baeza, & Muñoz-Reyes, 2016; Valls, Puigvert, Melgar, & Garcia-Yeste, 2016). There is a dearth of evidence-based sexual-assault prevention, and bystander programs are one of the few strategies with some demonstrated efficacy at US universities (Banyard, Moynihan, & Crossman, 2009; Mabry, A., & Turner, M. M., 2015).…”
mentioning
confidence: 99%
“…There have been limited population level surveys exploring the unique characteristics of, and influences on university students’ health in Australia 7‐9 . While issues such as alcohol consumption, tobacco use, sexual health and mental health have been individually investigated, few have been collected within a comprehensive survey of health issues using an online tool 5,10‐12 . However, comprehensive university student health survey data have been collected elsewhere, including the United States (US), Canada, United Kingdom (UK) and Ireland 13‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] While issues such as alcohol consumption, tobacco use, sexual health and mental health have been individually investigated, few have been collected within a comprehensive survey of health issues using an online tool. 5,[10][11][12] However, comprehensive university student health survey data have been collected elsewhere, including the United States (US), Canada, United Kingdom (UK) and Ireland. [13][14][15][16] These surveys have included topics from a range of health issues and risk factors, including student wellbeing, alcohol and tobacco use, mental health, sexual health, physical activity and nutrition.…”
mentioning
confidence: 99%